2023
DOI: 10.1002/pen.26354
|View full text |Cite
|
Sign up to set email alerts
|

A robust and fluorescent nanocomposite hydrogel with an interpenetrating polymer network based on graphene quantum dots

Abstract: Herein, a robust and fluorescent nanocomposite hydrogel polyvinyl alcohol/poly(N‐methylol acrylamide)/graphene quantum dots (PVA/PNMA/GQDs) with interpenetrating polymer network was made‐up by in‐situ radical polymerization and freeze–thaw method simultaneously. Because of GQDs trapped within the gel matrix as a result of the potent hydrogen bonds generated among PVA, PNMA, and GQDs, the nanocomposite hydrogel with an interpenetrating polymer network displayed strong fluorescence and enhanced mechanical proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…These hydrogels are structured with an interpenetrating polymer network, bolstering their mechanical strength and fluorescence capabilities, thus enabling the selective detection of Fe 3+ ions. Incorporating graphene quantum dots within the polymer network not only enhances its fluorescence but also markedly augments the mechanical properties of the hydrogel, positioning it as an excellent option for sensitive and selective ion sensing applications [55].…”
Section: Environmental Sensing and Remediationmentioning
confidence: 99%
See 1 more Smart Citation
“…These hydrogels are structured with an interpenetrating polymer network, bolstering their mechanical strength and fluorescence capabilities, thus enabling the selective detection of Fe 3+ ions. Incorporating graphene quantum dots within the polymer network not only enhances its fluorescence but also markedly augments the mechanical properties of the hydrogel, positioning it as an excellent option for sensitive and selective ion sensing applications [55].…”
Section: Environmental Sensing and Remediationmentioning
confidence: 99%
“…In nano-and microscale engineering, the encapsulation of quantum dots and the use of microfluidics showcase precision engineering trends in augmenting hydrogel functionality, particularly in sensing and detection, illustrating their versatility in identifying substances ranging from metal ions to biomolecules [44,[47][48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Introductionmentioning
confidence: 99%
“…The involved GQDs exhibit strong fluorescence and good mechanical properties, and the prepared nanocomposite hydrogel can emit stable bright-blue fluorescence under 365-nm radiation and is Fe 3 + selective while exhibiting excellent mechanical properties. [33] Notably, studies have shown that not all polymer organogels are very simple to crosslink. Moreover, few studies have been conducted on polymer organogel-based ALHSs; therefore, the design and construction of polymer organogel-based ALHSs remain difficult.…”
Section: Introductionmentioning
confidence: 99%
“…For decades, various fillers have been incorporated into PVA films and their structure-property relationship has been investigated. GQDs have also been used as fillers in PVA matrices and the enhancement of their luminescence properties has been explored [ 2 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the SPM data have been significantly related to photoluminescence (PL) emission results, which is of extreme relevance. Although the photoluminescence of GQD fillers within PVA matrices has already garnered significant interest [ 2 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], a thorough investigation of the nanostructural modifications occurring at the surface of PVA/GQD nanocomposites is still lacking. Understanding and manipulating the nanostructure of these films is crucial for tailoring their properties, constituting a fundamental step toward harnessing the full potential of these materials for practical use.…”
Section: Introductionmentioning
confidence: 99%